2016
DOI: 10.1158/1055-9965.epi-15-1290
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Human Papillomaviruses and Squamous Cell Carcinoma of the Skin: Nested Case–Control Study

Abstract: Background: Cutaneous human papillomavirus (HPV) types have been associated with non-melanoma skin cancer (NMSC), including a previous nested case-control study using HPV serology with bacterially derived fusion proteins with the major HPV capsid protein L1 (GST-L1). However, HPV serology using conformationally intact pseudovirions has been shown to correlate better with natural infection. Prospective studies using a more valid marker of infection are therefore warranted.Methods: Cancer registry follow-up of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The prevalence in our study was higher than that found by Biliris et al (27%), who detected HPV infection by classic PCR using only GP5+ and GP6+ primers. Moreover, most studies using tumor biopsy specimens as material for HPV DNA detection showed a lower prevalence of HPV infection than those using serology; this could be explained by possible degradation of DNA isolated from paraffin‐embedded tissues, leading to false‐negative results even though beta globin, used as control for amplification, was positive …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence in our study was higher than that found by Biliris et al (27%), who detected HPV infection by classic PCR using only GP5+ and GP6+ primers. Moreover, most studies using tumor biopsy specimens as material for HPV DNA detection showed a lower prevalence of HPV infection than those using serology; this could be explained by possible degradation of DNA isolated from paraffin‐embedded tissues, leading to false‐negative results even though beta globin, used as control for amplification, was positive …”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous HPVs are the most commonly identified HPV types in skin cancer; but mucosal HPV (mHPV) types have been also widely investigated in skin carcinogenesis, in view of their frequent involvement in cervical cancer . mHPVs act as an oncogenic factor by degradation of two principal proteins: tumor protein 53 (TP53) (involved in the regulation of cell cycle, apoptosis, and maintenance of genomic stability) and the retinoblastoma protein (pRB) (involved in the inhibition of the G1 to S phase transition in the cell cycle) .…”
Section: Introductionmentioning
confidence: 99%
“…Case‐control studies in both OTR and immunocompetent populations have shown that the presence of βPV DNA or antibodies was associated with a 1.5‐ to 3‐fold increased risk of cSCC 12, 20, 21, 22, 23, 24, 25, 26, 29, 31, 32. It was not possible, however, to determine whether the βPV infection increases risk of cSCC development or whether cSCC formation promotes active proliferation of βPV.…”
Section: Introductionmentioning
confidence: 99%
“…9,13 A substantial body of epidemiologic data show an association between HPV infection and cSCC, 12,[20][21][22][23][24] in particular, in OTRs. 25,26 In most studies, HPV infection has been determined by detection of serologic responses to a large series of βPV and sometimes γPV types 12,[21][22][23][25][26][27][28][29][30][31] and less frequently by detecting genomic DNA from 1 or multiple HPV types in eyebrow hair or skin scrapings. 20,21,25,[32][33][34] Case-control studies in both OTR and immunocompetent populations have shown that the presence of βPV DNA or antibodies was associated with a 1.5-to 3-fold increased risk of cSCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation